FROM ART TO PART: A SIMULTANEOUS GEOMETRY AND DECORATION WORKFLOW - Jiang, Yajie (My University, 2009)
Reproduction of hand crafted 3D shape geometry is an important industrial concept design step employed for items ranging in size and function. Adding surface art work can extend concept design to include essential product information. This thesis describes an equipment and workflow implementation for reproducing both 3D shape and art work. The hand crafted sample shape is laser digitized to obtain the XYZ geometry coordinates simultaneously with the surface gray level. The resulting point cloud is processed and converted to an STL format for plastic rapid prototyping, while the surface gray level information is treated to fit the smoothed surface, and match the reproduction ink jet printing system resolution and specification. Developed software automatically calculates the dot pattern to reproduce the art work onto the correct prototyped surface location.
Keywords: Mechanical Engineering; Mechanical Engineering